EFFECT OF PRODUCT QUALITY, PRICE ANDPURCHASE DECISION OFCONSUMER LOYALTYBLACKBERRY PHONE (Studies inUnisbank StudentsIn Semarang) - Ari Fahrudin, 09.05.51.0060; Moelatsih, Moelatsih (Students Journal of Economic and Management, 2014)
Today information technology is that it takes a lot of people mobile phones. Besides functioning to make and receive phone calls, cell phones are generally also has the function of sending and receiving short messages (short message service, SMS). Currently circulating various brands of mobile phones (cell phones) in the market, including, Nokia, Samsung, Blackberry, Sony Ericsson. Among the brands of mobile phones, Blackberrys market share in the years 2011 - 2012 has decreased. It is alleged consumer loyalty to Blackberry tends to be low. Loyalty is low due to the purchase decision Blackberry too low. Many factors affect a decrease in the purchase, such as product quality and price are not in accordance with the wishes of consumers. The population in this study was a university Stikubank (Unisbank), Tri Lomba Juang street and Kendeng V Bendan Ngisor street, Semarang Blackberry mobile phone users. The sample in this study was 100 students. Type and sampling techniques using puposivel sampling. Data collection techniques used were primary analysis technique used is multiple regression analysis. The results showed that: (1). Product quality influence on purchase decisions. (2). Price influence on purchase decisions. (3). Influence purchasing decisions on consumer loyalty. (4). Affect product quality on consumer loyalty. (5). Price effect on customer loyalty. (6). Affect product quality to customer loyalty with the purchase decision as mediation. (7). Price effect on consumer loyalty to the purchase decision as mediation.Keywords: Quality of Product, Price, Purchase Decision, Consumer Loyalty